2023
DOI: 10.3389/fgene.2023.1160599
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of super enhancer-induced PRR7-AS1 as a potential prognostic and immunological biomarker

Abstract: Introduction: Systematic pan-cancer analysis of the roles and regulatory mechanisms for PRR7-AS1 is currently not available.Methods: In the present study, a comprehensive bioinformatic approach was used to mine the underlying oncogenic effects of PRR7-AS1, including expression status, prognostic value and immune characteristics.Results: We discovered that PRR7-AS1 expression was remarkably upregulated in most cancer types and exhibited a negative correlation with the prognosis. Furthermore, PRR7-AS1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Li et.al found SE-TM4SF1-AS1 was negatively related with immune cell infiltration and was responsible for T cell-mediated immune response in STAD [ 15 ]. Meanwhile, our latest study demonstrated that SE-PRR7-AS1 expression was inversely connected with tumor-infiltrating immune cells and had a better predictive value for immunotherapy efficacy compared to other biomarkers [ 46 ]. All of these researches indicated some SE-lncRNAs could be related with an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Li et.al found SE-TM4SF1-AS1 was negatively related with immune cell infiltration and was responsible for T cell-mediated immune response in STAD [ 15 ]. Meanwhile, our latest study demonstrated that SE-PRR7-AS1 expression was inversely connected with tumor-infiltrating immune cells and had a better predictive value for immunotherapy efficacy compared to other biomarkers [ 46 ]. All of these researches indicated some SE-lncRNAs could be related with an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%